Pengaruh Insentif Finansial dan Lingkungan Kerja Fisik Terhadap Loyalitas Karyawan PT. Jasaraharja Putera Cabang Denpasar - Ossy Sapaynarta, A.A Made; Sagung Kartika Dewi, A. A (E-Jurnal Manajemen; Vol 2 No 2 (2013), 2013)
to investigate the effect of financial incentives and physical work environment on employee loyalty PT. Jasaraharja Putra Branch Denpasar is goal for this study. To achieve these objectives, research and data collection of financial incentives, physical work environment, and employee loyalty. The tools used to process data by multiple linear regression analysis test-f and the t-test. The results of this study are: simultaneous test results show that financial incentives and physical work environment significantly affect employee loyalty PT. Jasaraharja Putra Denpasar branch in the period with a value of Adj. R Square of 80.4 percent. The test results indicate that the variable partial financial incentives (X1) and physical environment (X2) have a positive and significant impact on employee loyalty PT. Jasaraharja Putra Branch Denpasar. This can be evidenced from tcount greater than the value of TTable. In the partial correlation test got the result that financial incentives are the dominant variables affecting employee loyalty variable PT. Jasaraharja Putra Branch Denpasar with value 0.649 or 64.9 percent Keywords: Financial Incentives, Physical Work Environment, Loyalty, Employee